(untitled) (Journal of Universal Science Research, 2024)
This article develops the following problems and educational technologies related to education including: The unique role of physics in human life in the world, the creation of favorable conditions for the lives of all citizens living in our country in the training of technical personnel in higher education institutions, especially technical universities, practical technological and pedagogical processes, professional self-activation, non-standard solutions technologies form the basis of the article in the development of educational technology development education based on a competency-based approach with special emphasis on the professional component